Development of Augmented Reality-Based Financial Management Learning Module to Enhance Student Engagement - Silalahi, Sondang Aida; Haryadi, Haryadi; Nurwendari, Weny; Herliani, Rini; Sitompul, Haryani Pratiwi (Universitas Pendidikan Mandalika, 2025)
This research aims to develop a valid, practical, and effective Financial Management learning module that incorporates Augmented Reality to enhance student engagement and improve comprehension. The study follows the 4D development model, which includes defining, designing, developing, and disseminating stages. The subjects were students from the 2021/2022 cohort of the Accounting Education Study Program at Universitas Negeri Medan who enrolled in the Financial Management course. Data collection involved expert validation surveys, user trials, and analysis of students' learning outcomes. Qualitative and quantitative analysis were used to evaluate the validity, practicality, and effectiveness of the module. Findings show that media and content experts highly rated the module, giving it strong validity and practicality scores. The module was also effective in enhancing students' understanding of financial management, as evidenced by significant improvements in t-test results. This Augmented Reality-based module is a highly innovative and effective learning resource for higher education.